Analisis Pengaruh Faktor Individu, Budaya Organisasi dan Insentif terhadap Kinerja Pegawai pada Sekretariat Daerah Kabupaten Aceh Tenggara - Syahputra, Jalaluddin Ibrahim; Lubis, Yusniar; Hartono, Budi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study is the result of a quantitative study that aims to answer how individual factors, organizational culture, and incentives simultaneously and partially affect the performance of the employees of the Regional Secretariat of Southeast Aceh Regency. Research data were collected through initial observations and filling out a list of statements by respondents who were designated as samples in this study. Further analyzed by quantitative analysis. In the F test the results state that simultaneously there is a significant influence between Individual Factors (X1), Organizational Culture (X2), and Incentives (X3) on the Performance (Y) of the Regional Secretariat of Southeast Aceh Regency employees. The t-test shows that there is no significant impact of Individual Factors (X1) and Organizational Culture (X2) on Performance (Y). Meanwhile, there is a significant impact of Incentives (X3) on Performance (Y). So that the Incentive becomes the variable that has the most impact on performance. In line with the conclusions above, it is recommended to take a more performance-based approach through the application of fair rewards and sanctions (punishment) to the State Civil Apparatus at the Regional Secretariat of Southeast Aceh Regency.